A Simple and Accurate 3D Numerical Model for Laser Cladding. (4th November 2019) - Chien, Shih-Kai; Tsai, Kuo-Teng; Li, Yueh-Heng; Wu, Yu-Ting; Chen, Wen-Lih
Abstract : A simple numerical model has been proposed for laser cladding. The model does not involve complex techniques such as cell addition, moving mesh, or prescribing a clad profile with a certain polynomial function. Instead, a mass function has been introduced to register the clad mass deposition on substrate, and from which the clad-track height can be estimated. The model takes several operational parameters, laser power, laser-head speed, and clad powder feeding rate, into consideration and predicts clad-track geometry, dilution, and substrate temperature. Experiments using two different combinations of substrate and clad powder materials to lay single and multiple clad tracks were conducted to provide data for model validation. The results show that the present model returns good agreement with experimental clad profiles for single and multiple tracks.